2016
DOI: 10.1097/wnf.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam and Valproate Retention Rate in Juvenile Myoclonic Epilepsy

Abstract: Levetiracetam showed lower retention rate than VPA, primarily due to poorer seizure control during long-term follow-up. More LEV patients achieved myoclonic seizure freedom than VPA patients. In women younger than 35 years, LEV and VPA had comparable retention rate; therefore, LEV could be a good option for women with JME with prominent myoclonic seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…This study confirmed that LEV had a certain effect on patients with JME. Although VPA had a better effect on GTCS control, which was consistent with another study, a recent study found that LEV and VPA showed similar retention rates, and LEV showed a good trend for MS control (36.7% [18/49] for VPA, 63.6% [14/22] for LEV, log rank P = 0.085) . In addition, a study reported the efficacy of LEV in GGE with MS .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study confirmed that LEV had a certain effect on patients with JME. Although VPA had a better effect on GTCS control, which was consistent with another study, a recent study found that LEV and VPA showed similar retention rates, and LEV showed a good trend for MS control (36.7% [18/49] for VPA, 63.6% [14/22] for LEV, log rank P = 0.085) . In addition, a study reported the efficacy of LEV in GGE with MS .…”
Section: Discussionsupporting
confidence: 82%
“…Although VPA had a better effect on GTCS control, which was consistent with another study, 23 a recent study found that LEV and VPA showed similar retention rates, and LEV showed a good trend for MS control (36.7% [18/49] for VPA, 63.6% [14/22] for LEV, log rank P = 0.085). 24 In addition, a study reported the efficacy of LEV in GGE with MS. 25 Some studies also reported a good efficacy and tolerability profile for LEV in the treatment of JME. 26,27 Above all, LEV may be a better option for women with JME in view of the side effects of VPA.…”
Section: Discussionmentioning
confidence: 99%
“…Postmarketing studies of BRV in predominantly focal epilepsies showed comparable retention rates of 51.5%, 72%, and 75.8% at 6 months . In GGE, sufficient data on retention rates are available for LTG, VPA, and LEV; with the highest retention rates for VPA in all GGE subsyndromes (90% at 3 years), followed by LEV (65% at 3 years; only juvenile myoclonic epilepsy) and LTG (45% at 3 years) …”
Section: Discussionmentioning
confidence: 91%
“…[38][39][40] In GGE, sufficient data on retention rates are available for LTG, VPA, and LEV; with the highest retention rates for VPA in all GGE subsyndromes (90% at 3 years), followed by LEV (65% at 3 years; only juvenile myoclonic epilepsy) and LTG (45% at 3 years). 46,47 Different factors point to BRV's potential as an alternative compound for treatment of SE. BRV is available as an intravenous solution and licensed for bolus injection.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium valproate (VPA) and levetiracetam (LEV) are extensively used anti-epileptic drugs in clinical practice, and both have satisfactory therapeutic effects and safety [22,23]. VPA plays an anti-epileptic role, mainly by enhancing the inhibitory neurotransmitter gamma aminobutyric acid (GABA) [24], and LEV plays an anti-epileptic role by combining synaptophysin with synaptic vesicle protein 2A (SV2A) [25].…”
Section: Introductionmentioning
confidence: 99%